Dealing with Resilience Conceptualisation. Formal Ontologies as a Tool for Implementation of Intelligent Geographic Information Systems - Lombardini, Giampiero (TeMA - Journal of Land Use, Mobility and Environment, 2014)
The paper addresses the issue of the representation of the concept of resilience (urban, environmental and landscape resilience) in the context of geographic information systems. In the current technical and scientific debate, resilience is configured as an intrinsic property of a system to switch from one equilibrium state to another without losing its basic internal structure, also definable in terms of "identity." The paths to success or stable growth as well as those of continuing and recursive crisis, although already explained in macroeconomic terms through the mechanisms of accumulation and multiplication (cumulative advantage), are also interpreted in terms of resilience. So, in the field of studies on spatial planning, the concept of resilience became particularly significant in an era characterized by great instability of social systems, deep economic and environmental crisis. In the process of urban and regional planning, conceive the development of an urban region in terms of resilience means using the logic of complex systems and then adapt in this way their methods of knowledge representation. The concept of resilience is multi-dimensional and vague, so its conceptualization is complex. The formal ontologies can be a useful tool to orient geographic information systems towards more complex forms of knowledge representation and to adapt them to the requirements of logic and formal complex systems, such as today’s urban regions.